Wireless sensor technology for continuous health monitoring of structures - Onoufriou, Toula; Kounoudes, Anastasis; Kalis, Antonis; Constantinides, Anthony G. (My University, 2010)
This paper gives an overview of continuous monitoring and local positioning principles for health monitoring of structures using wireless sensor networks, including recent results of the research project WiseSPOT (Novel wireless sensor nodes with smart antennas for localization of faults in structures). A novel approach for the development of a new generation of miniature low-powered wireless sensor nodes that will utilize advanced smart antenna technology for continuous monitoring, localization and tracking of events in is presented. Furthermore, the results of a first demonstrator of an optimized directional antenna add-on board are presented.
Keywords: Electric network synthesis; Wireless sensor networks; Health monitoring series